2013
DOI: 10.7763/ijcea.2013.v4.318
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Process to Prepare Silica Aerogel Microparticles from Rice Husk Ash

Abstract: Abstract-Biocompatible silica aerogel microparticles are promising drug delivery vehicles because of their large surface area and open pore structures. A simple process has been developed in this work to prepare silica aerogel microparticles from rice husk ash, using water-in-mineral oil emulsion for sol-gel, followed by aging in ethanol to strengthen gel network and drying with scCO 2 . This process obviates drawback of current methods for silica aerogels. The effects of speed of agitation of water-oil mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The fourth column in the L9 array of the Taguchi design was intentionally left blank to estimate the variance and the significance of the results. Table summarizes the different levels for each parameter; these levels were chosen based on our previous work and preliminary set of experiments . The response data were analyzed with the Minitab 15 statistical software.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fourth column in the L9 array of the Taguchi design was intentionally left blank to estimate the variance and the significance of the results. Table summarizes the different levels for each parameter; these levels were chosen based on our previous work and preliminary set of experiments . The response data were analyzed with the Minitab 15 statistical software.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarizes the different levels for each parameter; these levels were chosen based on our previous work and preliminary set of experiments. 13 The response data were analyzed with the Minitab 15 statistical software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are used as a fuel in some regions, in other countries they are treated as waste, they are usually disposed of by burning in the field, which results in damage to the either and the environment [1,2]. It was found that RH contains good amounts of amorphous porous silica, containing about 15-20 % silica [3][4][5]. High levels of silica content have encouraged many researchers to research how amorphous silica is extracted with high purity [5].…”
Section: Introductionmentioning
confidence: 99%